Methods of Blood Oxygen Level-Dependent Magnetic Resonance Imaging Analysis for Evaluating Renal Oxygenation - Fen Chen; Shulin Li; Dong Sun (Karger Publishers, 2018)
Blood oxygen level-dependent magnetic resonance imaging (BOLD MRI) has recently been utilized as a noninvasive tool for evaluating renal oxygenation. Several methods have been proposed for analyzing BOLD images. Regional ROI selection is the earliest and most widely used method for BOLD analysis. In the last 20 years, many investigators have used this method to evaluate cortical and medullary oxygenation in patients with ischemic nephropathy, hypertensive nephropathy, diabetic nephropathy, chronic kidney disease (CKD), acute kidney injury and renal allograft rejection. However, clinical trials of BOLD MRI using regional ROI selection revealed that it was difficult to distinguish the renal cortico-medullary zones with this method, and that it was susceptible to observer variability. To overcome these deficiencies, several new methods were proposed for analyzing BOLD images, including the compartmental approach, fractional hypoxia method, concentric objects (CO) method and twelve-layer concentric objects (TLCO) method. The compartmental approach provides an algorithm to judge whether the pixel belongs to the cortex or medulla. Fractional kidney hypoxia, measured by using BOLD MRI, was negatively correlated with renal blood flow, tissue perfusion and glomerular filtration rate (GFR) in patients with atherosclerotic renal artery stenosis. The CO method divides the renal parenchyma into six or twelve layers of thickness in each coronal slice of BOLD images and provides a R2* radial profile curve. The slope of the R2* curve associated positively with eGFR in CKD patients. Indeed, each method invariably has advantages and disadvantages, and there is generally no consensus method so far. Undoubtedly, analytic approaches for BOLD MRI with better reproducibility would assist clinicians in monitoring the degree of kidney hypoxia and thus facilitating timely reversal of tissue hypoxia.